Public Health Education in Pakistani Schools: A Critical Discourse Analysis through Textbooks and Extracurricular Activities - Ayesha Ikhlaq; Adeela Rehman; Wajiha Kanwal (JCTE, 2026)
This study examines how public health education is constructed and communicated in Pakistani primary schools through textbooks and extracurricular activities. Using a qualitative design grounded in Critical Discourse Analysis, the study analyzes grades 1–5 textbooks alongside semi-structured interviews with teachers and focus group discussions with students in six public and private schools in Rawalpindi and Islamabad. Findings reveal that health discourse in textbooks is narrowly framed around physical activity, sports, and hygiene, while key domains such as nutrition, oral health, mental well-being, illness prevention, and sexual and reproductive health remain marginalized or silenced. Although private schools offer more extracurricular activities than public schools, these are largely disconnected from explicit health education objectives, while public schools face significant resource constraints. The study concludes that Pakistani schools have not adequately adapted to contemporary public health needs and emphasizes the need for curriculum reform, teacher training, and structured, discourse-informed health education strategies to foster holistic and equitable health outcomes for children.